Long‐Term Sediment Export Estimates from Northern Jordan using Roman Cisterns as Sediment Traps. Issue 4 (July 2015) - Kraushaar, Sabine; Ollesch, Gregor; Siebert, Christian; Vogel, Hans‐Joerg; Fuchs, Markus
<x xml:space="preserve">Abstract</x> Roman cisterns served as rainwater storage devices for centuries and are densely distributed in parts of northern Jordan. A major earthquake hit the region ca. A.D. 750 and in a short time many settlements were abandoned. As a consequence, most cisterns were not maintained, and they filled with sediments that today provide a postabandonment depositional record. In two field surveys, we mapped the locations of more than 100 cisterns in the Wadi Al‐Arab basin and selected two for detailed stratigraphic analysis that included 14C and optically stimulated luminescence dating. Catchment basin area for each cistern was determined by differential GPS. Both cisterns filled with sediments after the great earthquake and consequent abandonment of the region. Calculated sediment volumes are translated to long‐term average sediment export rates of 2.6–6.6 t ha−1a−1, which are comparable to erosion and sediment yield rates from other studies within the Mediterranean region. Our pilot study suggests that this approach can be applied elsewhere to calculate long‐term sediment export rates on hill slopes containing relict cisterns.